Metabolismo intermediario basal y postprandial en diabetes mellitus tipo 2 a nivel del mar y altura - Garmendia, Fausto (2019)
Objective: To study and to compare the basal and postprandial intermediary metabolism of patients with diabetes mellitus type 2 (DM2) both at sea level (SL) as well as at high altitude (HA). Methodology: a total of 33 normal dwellers and 33 DM2 patients of SL(Lima, 150 meters above sea level- masl-) and 30 normal dwellers and 28 DM2 patients of HA(Cusco, 3,395 masl), of both genders, 40 to 70 years old were included. Body mass index (BMI) and abdominal circunference (AC) were measured. Glucose (G), total cholesterol (TC), HDL cholesterol (HDL), triglycerides (Tg), insulin (I) and non-esterified fatty acids (NEFA) were measured in blood at fasting, Cholesterol VLDL,LDL, NOHDL and HOMA coefficient were calculated; thereafter and during 6 hours after ingestion of a standardized mixed meal containing 730 Kcal G, I, Tg and NEFA were measured in blood. Statistical calculations were done by means of SPSS.v 23 program. Results: SLdiabetics had higher BMI, AC, G, Tg and HOMA values than normal dwellers. HA diabetics had higher weight, BMI, AC, G, Tg, VLDL and HOMA values than normal HA dwellers. HAdiabetics presented higher Tg and NEFAconcentrations than SLdiabetics. Conclusions: Diabetes mellitus impairs the basal and postprandial intermediary metabolism both at SL as well as at HA. At HA Tg and NEFA alterations were more marked.